ASSOCIATION BETWEEN BREASTFEEDING AND OVERWEIGHT/OBESITY IN SCHOOLCHILDREN AGED 7-14 YEARS - Wagner,Katia Jakovljevic Pudla (2021)
ABSTRACT Objective: To evaluate the prevalence of breastfeeding (BF) and the association between occurrence/duration of BF and overweight/obesity in schoolchildren aged 7-14 years. Methods: This is a cross-sectional study, conducted in 2012-2013, on schoolchildren aged 7-14 years from Florianópolis, Santa Catarina, Southern Brazil. Weight and height were measured according to procedures of the World Health Organization. Breastfeeding and sociodemographic data were obtained from a questionnaire responded by parents/guardians. BF was categorized as a dichotomous variable (yes/no) and according to duration (months). Nutritional status was evaluated according to the Z score of the body mass index per age for sex and it was categorized into two groups: normal weight (<Z score+1) and overweight/obesity (≥Z score+1). The adjusted analysis was performed by logistic regression in two age strata (age groups of 7-10 and 11-14 years). Results: 6.6% of schoolchildren had never breastfed; 16.8% had been breastfed for ≤3 months; 16.7%, for 4-6 months; and 59.9%, for ≥7 months. No statistically significant differences were found in the occurrence and duration of BF between the age groups. The prevalence of overweight/obesity was 34.2%. For age groups (7-10 and 11-14 years), the prevalence of overweight/obesity was 36.7% and 29.8%, respectively. Chance of overweight/obesity for the age group of 7-10 years was lower among schoolchildren who were breastfed (OR=0.54; 95%CI 0.33-0.88), when compared with those who never breastfed. When categorized, the chance of overweight/obesity in the age group of 7-10 years was lower for duration of BF ≤3 months (OR=0.41; 95%CI 0.20-0.83), and 4-6 months (OR=0.48; 95%CI 0.28-0.82) when compared with children who never breastfed. Conclusions: BF for at least six months was associated with a lower chance of overweight/obesity for schoolchildren aged 7-10 years. No association was found for schoolchildren aged 11-14 years.